Reliability of Multicast Under Random Linear Network Coding - Tsimbalo, Evgeny; Tassi, Andrea; Piechocki, Robert J. (IEEE transactions on communications, 2018)
We consider a lossy multicast network in which the reliability is provided by means of random linear network coding. Our goal is to characterize the performance of such network in terms of the probability that a source message is delivered to all destination nodes. Previous studies considered coding over large finite fields, small numbers of destination nodes or specific, often impractical, channel conditions. In contrast, we focus on a general problem, considering arbitrary field size and number of destination nodes, and a realistic channel. We propose a lower bound on the probability of successful delivery, which is more accurate than the approximation commonly used in the literature. In addition, we present a novel performance analysis of the systematic version of RLNC. The accuracy of the proposed performance framework is verified via extensive Monte Carlo simulations, where the impact of the network and code parameters are investigated. Specifically, we show that the mean square error of the bound for a ten-user network can be as low as 9 · 10 -5 for non-systematic RLNC.